Pengembangan Badan Usaha Milik Desa Usaha Jaya Makmur Desa Kerta Bumi Kecamatan Kuaro Kabupaten Paser - Rina Wahyuningtyas; Jauchar B; Budiman (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
This research is located in Kerta Bumi Village, Kuaro District, Paser Regency. This study aims to determine the efforts made by the chairperson and members of BUMDesa in developing the village-owned enterprise organization Usaha Jaya Makmur, starting from taking advantage of opportunities, optimizing carried out in each business unit, and recruiting BUMDesa management. With a research focus, namely the utilization of opportunities, optimization, and recruitment. Data collection techniques used are observation, interviews, and documentation. From the results of the study it was found that the efforts made by BUMDesa management in BUMDesa development were going well, this was shown by the increase in business units in BUMDesa by taking advantage of existing opportunities and BUMDesa which maximized each business unit so that it continued to run well and get good response from the community. Furthermore, recruitment was carried out by means of village meetings which were attended by village officials, BPD, RT heads, and several members of the community. From the recruitment that was carried out, it produced leaders and members who had good performance and cooperation, thereby encouraging smooth development of BUMDesa. Where they trust each other and are open to each other's proposals. On the other hand, it can be said that the BUMDesa chairman carries out his duties well where he is not only the initiator of ideas, but the chairman also participates in all activities carried out by BUMDesa members.